Migration theory as social theory: from transnational migration to mobile social ontologies - Ehrenfeld, Coretta (European journal of social theory, 2024)
With the paradigm shift toward transnationalism in the 1990s, perspectives on the phenomenon of migration changed fundamentally. Up to that point, the societies of origin and settlement had defined the analytical framework for sociology in general and migration research in particular. With the transnational migration model, this perspective made a U-turn: the transnational social networks of migrants became the starting point of migration research and social analysis. First, that meant that migrants and migrating people came to occupy a social-theoretical subject position. Second, migrant lives and the transnational social worlds that they sustain provided a social and socio-theoretical research perspective: migration itself became a perspective of social analysis in general. What does this imply for social theory? I suggest thinking about a social theory that is a migration theory at the same time—and vice versa. Therefore, I investigate Gilles Deleuze and Félix Guattari's nomadology as a specific kind of theory of social mobilities (Deleuze & Guattari, 1987). Within that framework, it is possible to describe social mobilities beyond the “physical” dichotomy between “sedentary” on the one hand and “mobile” or “migrant” on the other.